Heterogeneity in lending and sectoral growth: evidence from German bank-level data - Andrea Schertler; Claudia M. Buch; Natalja von Westernhagen (Deutsche Bundesbank, 2006)
This paper studies the sectoral and geographical dimensions of the response of bank lending to sectoral growth. We use several bank-level datasets provided by the Deutsche Bundesbank for the 1996-2002 period. Our results show that bank heterogeneity affects how lending responds to domestic sectoral growth. We document that banks? total lending to German firms reacts procyclically to domestic sectoral growth, while lending exceeding a threshold of ?1.5 million to German and foreign firms does not. Moreover, we find that the response of lending depends on bank characteristics such as the banking groups, the banks? asset size, and the degree of sectoral portfolio concentration. We find that total domestic lending by savings banks and credit cooperatives (including their regional institutions), smaller banks, and banks whose portfolios are heavily concentrated in specific sectors responds positively and, in relevant cases, more strongly to domestic sectoral growth.
Keywords: F3; G21; 330; bank lending; heterogeneity; sectoral growth; Kreditgeschäft; Branchenentwicklung; Schätzung; Deutschland